2021
DOI: 10.1038/s41598-021-99708-9
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA SNP-panel data suggests stability in bluefin tuna genetic diversity despite centuries of fluctuating catches in the eastern Atlantic and Mediterranean

Abstract: Atlantic bluefin tuna (Thunnus thynnus; BFT) abundance was depleted in the late 20th and early 21st century due to overfishing. Historical catch records further indicate that the abundance of BFT in the Mediterranean has been fluctuating since at least the 16th century. Here we build upon previous work on ancient DNA of BFT in the Mediterranean by comparing contemporary (2009–2012) specimens with archival (1911–1926) and archaeological (2nd century BCE–15th century CE) specimens that represent population state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…Future efforts may improve this by using capture-based enrichment to extract and genotype nuclear markers to test for changes in genetic variation (Carpenter et al 2013 ). Our findings do correspond with similar observations based on nuclear markers in Atlantic cod ( G. morhua ), Atlantic bluefin tuna ( Thunnus thynnus ), and Pacific herring ( Clupea pallasi ), which showed that exploitation has not yet led to detectable losses of genetic diversity (Andrews et al 2021 ; Martínez-García et al 2021 ; Moss et al 2016 ; Pinsky et al 2021 ; Speller et al 2012 ). Together these studies suggest that heavily exploited species do not appear to have lost any appreciable amounts of genetic diversity.…”
Section: Discussionsupporting
confidence: 90%
“…Future efforts may improve this by using capture-based enrichment to extract and genotype nuclear markers to test for changes in genetic variation (Carpenter et al 2013 ). Our findings do correspond with similar observations based on nuclear markers in Atlantic cod ( G. morhua ), Atlantic bluefin tuna ( Thunnus thynnus ), and Pacific herring ( Clupea pallasi ), which showed that exploitation has not yet led to detectable losses of genetic diversity (Andrews et al 2021 ; Martínez-García et al 2021 ; Moss et al 2016 ; Pinsky et al 2021 ; Speller et al 2012 ). Together these studies suggest that heavily exploited species do not appear to have lost any appreciable amounts of genetic diversity.…”
Section: Discussionsupporting
confidence: 90%
“…There are uncertainties on reports of BFT eggs and larvae found in the Black Sea (Di Natale, 2015; Mather et al, 1995), although adaptation to spawn this low‐salinity environment is possible for BFT (MacKenzie & Mariani, 2012) and adults have been found in the Black Sea with ripe gonads (Di Natale, 2015). Genomic analysis is required to exclude the possibility that Black Sea BFT represented a separate spawning population but since preliminary genetic results (Andrews et al, 2021) did not support this theory and juveniles have never been caught in this region (Di Natale, 2015), we find it more likely that the Black Sea migration and the Marmara Sea residency was a prey‐dependent, learned behaviour, as part of a collective memory, which takes time to rebuild (De Luca et al, 2014; Petitgas et al, 2010). Regardless, the return of Black Sea BFT will depend heavily on the recovery of ecosystems and trophic cascades in the Marmara Sea, Black Sea and Azov Sea, which remain poor after overexploitation (Demirel et al, 2020; Ulman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…From the 15th c., Bosphorus trap fisheries recorded BFT migrations into the Black Sea from April, with the majority believed to return to the Marmara Sea or Aegean Sea by September, due to poor winter conditions (Cort & Abaunza, 2019;. We consider it likely that low δ 13 C, δ 15 N and δ 34 S values in BFT from Istanbul were promoted by autumn or winter foraging in the Marmara or Black Sea, as predicted by early-20th c. scientists (Devedjian, 1926;Sara, 1964) Genomic analysis is required to exclude the possibility that Black Sea BFT represented a separate spawning population but since preliminary genetic results (Andrews et al, 2021) did not support this theory and juveniles have never been caught in this region (Di Natale, 2015), we find it more likely that the Black Sea migration and the Marmara Sea residency was a prey-dependent, learned behaviour, as part of a collective memory, which takes time to rebuild (De Luca et al, 2014;Petitgas et al, 2010). Regardless, the return of Black Sea BFT will depend heavily on the recovery of ecosystems and trophic cascades in the Marmara Sea, Black Sea and Azov Sea, which remain poor after overexploitation (Demirel et al, 2020;Ulman et al, 2020).…”
Section: Bft Had An Isotopically Unique Black Sea Nichementioning
confidence: 99%
“…Atlantic bluefin exhibits strong natal homing behavior (Brophy et al, 2016;Boustany et al, 2008;Block et al, 2005) and is therefore managed as two separate stocks: the larger Eastern stock spawning predominantly in the Mediterranean, and a smaller Western stock spawning predominantly in the Gulf of Mexico (ICCAT, 2023). Recent studies, however, have demonstrated weak genetic divergence in Atlantic bluefin and the existence of a previously unknown spawning ground in the Slope Sea where the stocks seem to interbreed (Diaz-Arce et al, 2024;Aalto et al, 2023;Andrews et al, 2021;Rodríguez-Ezpeleta et al, 2019), thereby challenging the assumption of two reproductively isolated populations. After severe international overfishing of Atlantic bluefin in the last century, the Eastern Atlantic bluefin stock has at present efficiently recovered due to strict management measures and favorable oceanographic conditions in the recent decade (ICCAT 2022a, 2022b) followed by improved recruitment with a series of very strong year classes (Reglero et al 2018;Garcia et al 2013;ICCAT 2023).…”
Section: Introductionmentioning
confidence: 99%